POLA GERAKAN ISLAM GARIS KERAS DI INDONESIA - Eka Hendry Ar (The Pontianak State Institute of Islamic Studies, 2013)
The attack on the World Trade Center in September 2001 was a monumental and symbolic event that changed the way people view certain radical movements especially Islam. For some, this is a new symbol of threat described as “the Green Menace” (Islamic World) against the West. For others, this is a milestone of resistance to the Western civilization. This article aims at elaborating the development of Islamic hard line movements in the post WTC attack, its movement pattern, method of understanding religious doctrine, social segmentation of movement followers, and the initial condition which triggers the rise of religious radicalism.